Effects of upper cervical joints manipulation on the signs and symptoms of subjects with headache: a blind clinical trial. - Sakabe, Fabiana Forti; Sakabe, Daniel Iwai; Bortolazzo, Gustavo Luiz (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
There is a relationship between headaches and dysfunctions in the upper cervical spine, so joint manipulation in this region can be a useful tool for recovering tissue mobility and improving the related symptoms. Objectives: to evaluate the effect of 3 sessions of manipulation of the upper cervical spine on pain, cervical mobility, neck disability index (NDI) and the MIDAS questionnaire of subjects with headache. Methods: 13 subjects (28.1 ± 6.7 years) with headache participated. Initially, they filled in a pain diary for 4 weeks. After this period, NDI and MIDAS questionnaire were applied. Then, the cervical spine movements were measured with a tape measure, with the subject in the seated position. Subsequently, the intervention was performed (3 sessions with an interval of 7 days between them), with the subject positioned in the supine position and the global manipulation for the upper cervical spine was applied bilaterally. At the end of the intervention, subjects were re-evaluated for cervical mobility and for the NDI and MIDAS questionnaire. After that period, subjects answered the pain diary for another 4 weeks (follow up). The statistical analysis consisted of the KS normality test, followed by ANOVA test (and Tukey post hoc test) or paired Student’s t test, with the level of significance set at 5%. Results: MIDAS questionnaire and NDI showed a significant improvement after the cervical mobility intervention. The pain parameters, assessed by the pain diary, were significantly reduced during the intervention and remained so in the follow up evaluation. Conclusion: the intervention was effective in reducing the signs and symptoms of subjects with headache.